Revealing the Interest in Using Digital Banks by Generation Z in the Aspect of Technology Behavior - Ayu Bintang Wulandari; Gusi Putu Lestara Permana (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the interest in using digital banking using the Technology Acceptance Model theory. Methodology/approach: This research was conducted intentionally (Purposive Sampling) with the criteria of having used digital banking at least once and teenagers born between 1997 and 2012. Primary data sources were obtained from distributing questionnaires. Results/findings: The level of customer satisfaction with digital banking services shows a very high category, which means that most customers are satisfied with the quality of service, ease of access, and benefits provided by digital banks in meeting their transaction and financial management needs. Conclusion: The study demonstrates that perceived usefulness, ease of use, and security significantly influence the intention to adopt digital banking in Indonesia. These results confirm that users are more inclined to use digital banking when applications are beneficial, user-friendly, and secure. Theoretically, the study extends the Technology Acceptance Model (TAM) by integrating perceived security as a critical construct in the digital banking context. Limitations: The limitations of this study are that the time period and duration of digital banking use by consumers do not use a time limit, and repeated use of digital banking is still not visible. Contribution: This research contributes to the development of the Technology Acceptance Model (TAM) by adding security variables as an important factor in digital bank adoption, so that the technology acceptance model is more relevant in the context of modern financial services.